PENGARUH PERLAKUAN BENIH DENGAN AGENS HAYATI DAN PEMUPUKAN TERHADAP PERTUMBUHAN TANAMAN, PRODUKSI DAN MUTU BENIH PADI DI LAPANG - Agustiansyah Agustiansyah; Satriyas Ilyas; Sudarsono Sudarsono; Muhammad Machmud (Universitas Lampung, 2012)
Biological agents is believed to function as fitostimulators, biofertilizers, and biopesticides. These capabilities have been widely reported by researchers on various crops. Application these agents to rice plants had not been widely reported, particu-larly in Indonesia. The purpose of this study was to determine the effect of seed treatment with rhizobacteria and use of fertilizer P on plant growth, seed quality in the field. The study experiments that were conducted in Research Station of Indonesian Rice Research Institue, Sukamandi, West Java. The experimental results show that P fertilizer application at the rate of 50 kg ha-1 produced plant height, number of tillers, number of pithy grains, and total number of grains per panicle better than that 100 kg ha-1.. Seed treatments by immersion in a mixture of P. diminuta A6 + B. subtilis 5/B) with or without matriconditioning increased plant height and num-ber of tillers. Seed treatment with matriconditioning + biological agents increased the number of grains and total number of grains. All the seed treatments and P fertilizer applications no significantly affected the physi-ological quality of seed yield, but reduced population of Xanthomonas oryzae pv.oryzae (Xoo) in the seeds. Keywords: bactericide, biofertilizer, biopesticide, seed patologis quality